Introduced marine ecosystem engineers change native biotic habitats but not necessarily associated species interactions. (30th October 2020) - Cornelius, Annika; Buschbaum, Christian
Abstract: Introduced bioengineering organisms may fundamentally change native coastal ecosystems by modifying existing benthic habitat structures and thereby habitat-specific species interactions. The introduction of the Pacific oyster Magallana gigas into the sedimentary coastal area of the south-eastern North Sea and its preferred settlement on native blue mussel shells caused a large-scale shift from monospecific Mytilus edulis beds to current mixed reefs of mussels and oysters. To investigate whether the newly developed biotic habitat affects the occurrence of associated native key organisms and their ecological functions, we studied the long-term density trajectory of the gastropod Littorina littorea and its grazing activity on barnacles attached to Pacific oyster reefs in the northern Wadden Sea. We found no significant correlation between oyster and snail densities on blue mussel beds in the last two decades, which spans a time-period from the beginning of Pacific oyster establishment to today's oyster dominance. A manipulative field experiment revealed that snail density significantly affects the recruitment success of barnacles Semibalanus balanoides on oyster shells with the highest number of barnacle recruits at snail exclusion. Thus, density and grazing activity of the snail L. littorea may control barnacle population dynamics on epibenthic bivalve beds in the Wadden Sea. This interspecific interaction was already known for blue mussel beds before the oyster invasion and, therefore, we conclude that despite the strong modifications that non-native ecosystem engineers cause in native biotic habitats, the ecological functions of associated key species can remain unchanged. Graphical abstract: Image 1 Highlights: Population dynamics of native Littorina littorea were not affected by introduced oysters. Grazing by periwinkles constitutes an important factor for the occurrence of associated species in oyster reefs. Non-indigenous oysters found in Littorina littorea a native partner with mutual benefits.